Form and flexibility in phosphoinositide 3-kinases. (22nd July 2009) - Williams, Roger; Berndt, Alex; Miller, Simon; Hon, Wai-Ching; Zhang, Xuxiao
Abstract : PI3Ks (phosphoinositide 3-kinases) have important roles in a variety of cellular activities, including survival, proliferation, growth, shape, migration and intracellular sorting. Consistent with their function in cell survival and growth, the gene for the class Iα PI3K catalytic subunit is a common site of gain-of-function mutations in cancers. Ongoing structural studies of these enzymes and the complexes they make with their regulatory subunits have helped to clarify the mechanistic basis of this role in tumour development. The broad spectrum of biological activities associated with various isotypes of class I PI3Ks has led to an intense search for isotype-specific inhibitors as tools in mammalian cell biology and for therapeutic application. Structural studies of the class I PI3Ks suggest that flexibility may be a component of the catalytic cycle of the enzymes.